Aborsi dan Peraturannya di Indonesia Tahun 2023-2025: Sebuah Analisis Bioetika Kristen - Saragih, Denni Boy (Veritas : Jurnal Teologi dan Pelayanan, 2025)
Regulations regarding abortion have undergone significant changes since the enactment of Law No. 1 of 2023 on the Criminal Code, which contains provisions regarding the criminalization of abortion. There is an exception to the criminalization of abortion for victims of rape and sexual violence up to 14 weeks of pregnancy. The new context of these regulations presents specific pastoral and theological challenges. Through biblical, church history, and theological studies examining the Christian stance on abortion, this article proposes how the Christian faith can maintain its consistency in addressing the issue of abortion, namely, a high regard for the sanctity of human life from the moment of conception. The author also provides practical recommendations based on Christian bioethics, serving as an initial proposal for Protestant-Evangelical churches and communities in Indonesia in addressing this issue.